Changes of Blood Pressure in different Seasons of Bangladesh - Hoque, Md Harisul; Ahmed, Khurshed; Kabir, Mohammad Faisal Ibn; Fatema, Nilufar (University Heart Journal, 2021)
Abstract not available University Heart Journal Vol. 17, No. 2, Jul 2021; 86-90